Milestones in Personalized Medicine: From the Ancient Time to Nowadays—the Provocation of COVID-19 - Visvikis-Siest, Sophie; Theodoridou, Danai; Kontoe, Maria-Spyridoula; Kumar, Satish; Marschler, Michael (Frontiers in Genetics, 2020)
The first evidence of individual targeting medicine appeared in ancient times thousands of years ago. Various therapeutic approaches have been established since then. However, even nowadays, conventional therapies do not take into consideration individuals’ idiosyncrasy and genetic make-up, failing thus to be effective in some cases. Over time, the necessity of a more precise and effective treatment resulted in the development of a scientific field currently known as “personalised medicine”. The numerous technological breakthroughs in this field have acknowledged personalised medicine as the next generation of diagnosis and treatment. Although personalised medicine has attracted a lot of attention the last years, there are still several obstacles hindering its application in clinical practice. These limitations have come to light recently, due to the COVID-19 pandemic. This review describes the ‘journey’ of personalized medicine over time, emphasising on important milestones achieved through time. Starting from the treatment of malaria, as a first more personalised therapeutic approach, it highlights the need of new diagnostic tools and therapeutic regimens based on individuals’ genetic backround. Furthermore, it aims at raising global awareness regarding the current limitations and the necessity of a personalised strategy to overpass healthcare problems and hence, the current crisis.